2020
DOI: 10.1186/s12933-020-01081-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of coronary plaque volume change related to triglyceride glucose index: The Progression of AtheRosclerotic PlAque DetermIned by Computed TomoGraphic Angiography IMaging (PARADIGM) registry

Abstract: Background: The association between triglyceride glucose (TyG) index and coronary atherosclerotic change remains unclear. We aimed to evaluate the association between TyG index and coronary plaque progression (PP) using serial coronary computed tomography angiography (CCTA). Methods: A total of 1143 subjects (aged 60.7 ± 9.3 years, 54.6% male) who underwent serial CCTA with available data on TyG index and diabetic status were analyzed from The Progression of AtheRosclerotic PlAque DetermIned by Computed TomoGr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Accumulating evidence indicated that the elevated TyG index was linked to accelerated atherosclerosis. The study of Won et al ( 11 ) found that patients with elevated TyG index had a more remarkable increase in coronary plaque volume. The study of Lee et al ( 48 ) demonstrated that there was a >3-fold increase in the incidence of coronary artery stenosis in subjects with elevated TyG index.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accumulating evidence indicated that the elevated TyG index was linked to accelerated atherosclerosis. The study of Won et al ( 11 ) found that patients with elevated TyG index had a more remarkable increase in coronary plaque volume. The study of Lee et al ( 48 ) demonstrated that there was a >3-fold increase in the incidence of coronary artery stenosis in subjects with elevated TyG index.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a novel convenient biomarker of IR, Triglycerideglucose (TyG) index calculated by the formula ln [fasting triglycerides (mg/dl) × fasting plasma glucose (mg/dl)/2], has elicited the interests of researchers because of its superior performance in the estimation of IR than a homeostatic model assessment of IR (HOMA-IR) (6)(7)(8)(9). Certain studies in humans showed that TyG index was positively correlated with coronary artery calcification (10), coronary plaque progression (11), and subclinical myocardial injury (12), providing plausibility of the prognostic significance of TyG index in CAD. As a product of triglycerides and plasma glucose, the TyG index may provide additional information for the risk assessment of adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, insulin resistance led to the chronic inflammation [ 18 ], endothelium dysfunction [ 19 21 ], facilitated the formation of foam cells in the initiation of atherosclerosis [ 22 ] and promoted the vulnerable plaque [ 23 ]. Previous studies indicated that TyG index was associated with increased arterial stiffness in general population [ 24 , 25 ] and an independent predictive marker for plaque progress [ 26 ], which could contribute to the occurrence of stroke. Secondly, previous research showed that insulin resistance affected platelet adhesion, activation and aggregation [ 27 29 ] which were associated with artery stenosis or occlusion and involved in stroke occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Won et al . reported that the participants with the highest tertile TyG index had a 1.65-fold higher risk of coronary PP and 1.78-fold of rapid PP compared with the lowest tertile [ 34 ]. However, to our knowledge, little is currently known about the relationship between TyG index and arterial stiffness progression.…”
Section: Discussionmentioning
confidence: 99%